EXAMPLE OF PALEOSEBKHA LITTORAL DEPOSITS OF SENONIAN IN THE "BASINS ZONE" OF AIT OURIR (MARRAKECH HIGH ATLAS, MOROCCO) - Hadach, Fatiha; Algouti, Ahmed; Algouti, Abdellah; Mourabit, Zahra (European Scientific Journal, ESJ, 2015)
The comparative analysis of three cuts oriented West-East at the level of the basin of Jbel Sour, led to defining during the Santonian: A western sector of detrital coarse sediments, deposited in the context of a fluvial dynamics. Oriental sector of mainly carbonato- evaporite sedimentation, in a less deep and confined environment, subject to significant subsidence under a hot, arid climate favoring the formation of sebkha facies. These santonien deposits are organized in a regressive megasequence, surmounted by a Maastrichtian transgressive formation, corresponding, in this area, to a tidal-flats environment. This Maastrichtian serie marking the return of the epicontinental sea, under a hot, arid climate, by an Atlantic transgression encompassing the entire study area.